The Managerial Role of an Outstanding Principal in the Aspect of Educational Quality - Istikomah, Istikomah; Kusumaningsih, Widya; Sulianto, Joko (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to analyze the managerial role of an outstanding principal in improving the quality of early childhood education through the implementation of the management functions of planning, organizing, actuating, and controlling (POAC) at TK Islam Sultan Agung 1 Semarang, Indonesia. The study employed a qualitative approach with a case study design to gain an in-depth understanding of managerial practices within the natural context of the educational institution. Data were collected through in-depth interviews, observations, and document analysis involving the principal, teachers, the school committee, and parents. Data analysis was conducted interactively through the stages of data reduction, data display, and conclusion drawing, while the validity of the data was ensured through source and technique triangulation. The findings reveal that the principal implemented managerial functions in an integrated and systematic manner. Planning was carried out participatively by integrating Islamic values with national early childhood education standards. Organizing was conducted through competency-based task distribution and structured coordination among educators and staff. The implementation of programs was supported by collaborative leadership, continuous professional development, and a reflective culture that strengthened teachers’ professionalism. Controlling was performed through academic supervision and ongoing evaluation aimed at improving educational quality. In addition, transparency in resource management contributed to strengthening accountability and building public trust. The study concludes that effective and value-based managerial leadership plays a crucial role in fostering a sustainable culture of quality in Islamic-based early childhood education institutions and in ensuring the long-term development of the institution.